Barclay International A production system study - Pascual, Jose Jerome R. III.; Santos, Gerardo Oriel D.; Soriano, Jose Paolo A.; Valdes, Rafael Gerardo Uldarico A. Jr.; Raya, Lawrence T. (Diliman, Quezon City College of Engineering, 1985)
Barclay International is involved in the development, manufacturing and distribution of home care and institutionalized products; and personal care products. The company was formed in 1982 by a Filipino family who were out to prove that the Filipinos are capable in competing with companies if not to surpass them. In its effort to familiarize itself with its operation, the group made several plant visits for the purpose of observing, interviewing, and more importantly, data gathering. The group tried to follow its proposed schedule, however, unavoidable delays cropped up time and again. Observations of actual operations were made as the group eagle-eyed for symptoms of faulty layout or incorrect process lows. Some bottlenecks were observed specially in the packaging area. Our main contact person, Mr. Andy Bonifacio, the PPIC officer, provided use with helpful information. Through him, our group found out that methods employed by Barclay in forecasting the future demands, and consequently related them to production scheduling. Data, like the plant layout, organizational chart, process flows, time standards, etc. were made available to us. THe group measured the distances between departments to facilitate our determination of length traveled by raw materials, finished goods, and personnel within the work area. Equipped with our initial data and some mathematical tools provided in class and our previous I.E. subjects, the group attempted to analyze the production system of Barclay. In the process, the group discovered that it lacked several vital information, and these meetings prompted the group then, to make additional visits to the site. We lacked data about Barclay's products' past demands' history, unit costs of products and product composition. At first the company was reluctant to provide the group the needed information due to the efforts to keep such information confidential. However, the group was able to settle a compromise in which data we required were given in coded form. In addition to coding, actual values were modified to some percentage. As a result, our computations contain certain degrees of deviation from actual values. Analyzing further, the group identified some problems and inefficiency in the system and its processes. The group decided to concentrate on the following areas: production planning and scheduling, forecasting, production process improvement, layout analysis. it was discovered that the PPIC, in planning the production schedule, applies a certain degree of "guesswork" resulting in inaccurate production planning and some inventory shortages. It was also revealed that Barclay has not been employing any reliable forecasting method. Forecasts are just based on the past month's sales plus of minus speculated increase or decrease in demand. At the time our study started, the company had just moved to Makati from their Pasig Plant. Because of this, the group decided to look into the possibility of improving the layout they have adopted. Finally, the group looked into the possibility of improving the efficiency of the existing process. Regarding the company's production planning requirement, the group is recommending that the company familiarize itself with an appropriate linear-programming technique. Since the company has an EDP department, it can require for the design of software which they can run on their computer. A sample LP model is provided in this report using the product mix model. As to forecasting, the group applied Winter's forecasting method since the past demand data reflects a seasonal trend. The layout problem was tackled with the help of a REL chart developed by the group. CORELAP was used in determining an ideal layout. However, due to structural constrains and restriction on capital outlay, a less ideal layout was adopted. Next, we searched for inefficiencies in the production process. We found several (mostly in the packaging line) which we hoped to improve with our recommendations. Our recommendations invoked some modification of equipment, purchase or lease of equipment, employment of additional workers at certain stages and decrease in others. The main objective of our recommendations was to decrease production time to increase production capacity in the event demand increases. Finally, we made some observations regarding the working conditions. Our recommendations were directed towards the increased comfort and safety of workers, since the production lines of Barclay are predominantly labor intensive. This study will provide a more detailed picture of the company's operations, its problems and our recommendations.
Feasibility study
Keywords: Barclay International; Manufacturing industry; Production engineering